Nutrition-related habits and associated factors of Brazilian adolescents - Ferreira de Moraes, Augusto Cesar; Fernandes, Romulo Araujo [UNESP]; Destro Christofaro, Diego Giulliano; de Oliveira, Arli Ramos; Arasaki Nakashima, Alika Terumi; Reichert, Felipe Fossati; Falcao, Mario Cicero (Springer Basel Ag, 2010)
To investigate the nutrition-related habits (NRH) of Brazilian adolescents and evaluate the associations with risk factors.Cross-sectional school-based was carried out among high school adolescents aged 14-18 years (n = 1,759) from public and private schools from two cities. The NRH were investigated by the weekly consumption of vegetables, fruit, sweet food and fried food. Risk factors investigated were: city, sex, age, socioeconomic status and nutritional status. In statistics, Poisson regression was used with robust variance adjustment.Data indicated low consumption of fruits and vegetables, 70.0 and 71.0%, respectively, and high consumption of sweets and fried food, 66.7 and 63%, respectively. Boys showed risk of inadequate intake of vegetables [prevalence ratios (PR) 1.10, 95% CI 1.01-1.16] and fruit (PR 1.09, 95% CI 1.01-1.16). Furthermore, adolescents who live in Maringa had greater likelihood of consuming vegetables and fruit (20 and 25%, respectively). However, they presented risk of inadequate consumption of sweets (PR 1.19, 95% CI 1.11-1.28) for adolescents who live in Presidente Prudente.We concluded that inadequate NRH show high prevalence among adolescents and indicate the need to employ educational strategies that promote the adoption of more healthy habits and behaviors.
Keywords: Dietary; Epidemiology; Adolescent behavior; Questionnaires; Socioeconomic factors